A PORTRAITURE OF TEACHING TECHNIQUES AND VALUES PROPOSED IN DEAD POETS SOCIETY A MOVIE BY PETER WEIR - Tri Yulianingsih; Syafrianto SM; Maria Wulandari (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2021)
Dead Poets Society is a movie about teaching techniques and values that are applicable to teachers and students. The objectives of the research are to describe the teaching techniques and educational values proposed in this movie. This research uses a descriptive qualitative design. The data is obtained from the dialogues and events identified from the Dead Poets' Society movie, especially about teaching techniques and values. The researchers are the main players in this research who plan, collect, analyze, and report the data. Some activities were conducted to collect the data, namely: watching the movie, finding teaching techniques in the movie, classifying and writing the teaching techniques found; and coding the data. There are some teaching techniques and values found in this movie. They are, respectively, authentic material, reading aloud, questions and answers, positive suggestions, peer correction, graphic organizer, paragraph writing, role play, and creative adaptation. Meanwhile, there are some educational values reflected in this movie. They are religion (religosity), respect, responsibility, obedience, discipline, confidence, hard work, daring to take a risk, and politeness.